International best practice for the evaluation of responsiveness to sapropterin dihydrochloride in patients with phenylketonuria - Muntau, Ania Carolina (2019)
Phenylketonuria (PKU) is an inherited metabolic disease caused by phenylalanine hydroxylase (PAH) deficiency. As the resulting high blood phenylalanine (Phe) concentration can have detrimental effects on brain development and function, international guidelines recommend lifelong control of blood Phe concentration with dietary and/or medical therapy. Sapropterin dihydrochloride is a synthetic preparation of tetrahydrobiopterin (6R-BH4), the naturally occurring cofactor of PAH. It acts as a pharmacological chaperone, reducing blood Phe concentration and increasing dietary Phe tolerance in BH4-responsive patients with PAH deficiency. Protocols to establish responsiveness to sapropterin dihydrochloride vary widely. Two meetings were held with an international panel of clinical experts in PKU management to develop recommendations for sapropterin dihydrochloride response testing. At the first meeting, regional differences and similarities in testing practices were discussed based on guidelines, a literature review, outcomes of a global physician survey, and case reports. Statements developed based on the discussions were sent to all participants for consensus (>70% of participants) evaluation using a 7-level rating system, and further discussed during the second meeting. The experts recommend sapropterin dihydrochloride response testing in patients with untreated blood Phe concentrations of 360–2000 μmol/L, except in those with two null mutations. For neonates, a 24-h sapropterin dihydrochloride loading test is recommended; responsiveness is defined as a decrease in blood Phe ≥30%. For older infants, children, adolescents, and adults, a test duration of ≥48 h or a 4-week trial is recommended. The main endpoint for a 48-h to 7-day trial is a decrease in blood Phe, while improved Phe tolerance is the endpoint to be assessed during a longer trial. Longer trials may not be feasible in some locations due to lack of reimbursement for hospitalization, while a 4-week trial may not be possible due to limited access to sapropterin dihydrochloride or public health regulation. A 48-h response test should be considered in pregnant patients who cannot achieve blood Phe ≤360 μmol/L with a Phe-restricted diet. Durability of response and clinical benefits of sapropterin dihydrochloride should be assessed over the long term. Harmonization of protocols is expected to improve identification of responders and comparability of test results worldwide.